Survei Analisis Biomekanik Passing Pada Pemain Sepakbola Private Training Pati - Ahmad Badawi; Widiyanto; Ahmad Nasrulloh (Universitas Singaperbangsa, 2021)
Football is a sport where every player is required to have good technical skills. The player's technique is said to be good if it is carried out according to the principles of biomechanics disciplines, resulting in movement efficiency. In the process of passing the ball, there are several factors, namely the length of the forward swing trajectory, leg length, knee angle, knee angle of support and ball speed. basic pass (passing), required mastery of good technique. The coach can evaluate every passing movement using the principles of biomechanics. The purpose of this study was to evaluate the basic techniques of passing players from the Pati Private Training team which were grouped into three categories. The method used in this research is a survey method with a descriptive approach system. The data is processed in the form of videos taken with a 1200D DSLR camera from 3 samples of Pati Private Training players then video processing using the kinovea application. The results showed differences in the results of the three samples on the ability to pass the ball from the length of the forward swing track, heel length, knee angle, foot angle, speed